2018
DOI: 10.5713/ajas.17.0156
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with detoxified Rhus verniciflua sap on egg production, yolk lipid and intestinal microflora in laying hens

Abstract: ObjectiveThis study was conducted to investigate the effects of dietary detoxified Rhus verniciflua sap (RVS) on production performance, egg quality, lipid fractions of egg yolk, liver and serum, and the profile of cecal microflora in laying hens.MethodsTwo hundred 52-week-old Hy-Line Brown layers were randomly divided into 4 groups with 5 replicates per group (2 hens per cage, 5 cages per replicate) and were provided with one of 4 experimental diets containing 0%, 0.05%, 0.1%, or 0.2% RVS, for 6 weeks. Due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…In contrast, the low level of plant extracts in T1 have negative effect on the cholesterol level, which needs to be further evaluated. Sometimes, the decrease in egg cholesterol content had a negative effect on egg production [ 31 ], which was not observed in the present study. The cholesterol-lowering effects of MA and GT in farm and experimental animals were reported.…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…In contrast, the low level of plant extracts in T1 have negative effect on the cholesterol level, which needs to be further evaluated. Sometimes, the decrease in egg cholesterol content had a negative effect on egg production [ 31 ], which was not observed in the present study. The cholesterol-lowering effects of MA and GT in farm and experimental animals were reported.…”
Section: Resultscontrasting
confidence: 58%
“…Cholesterol in egg yolk is synthesized in the liver, secreted as very-low-density lipoprotein (LPL) in blood, and deposited via receptor-mediated endocytosis in yolk [ 32 ]. Thus, the decrease in cholesterol by MA and GT supplementation might be due to the consequences of altered endogenous lipoproteins (production or secretion) or/and cholesterol metabolism (i.e., synthesis, degradation, and distribution) [ 31 ]. Furthermore, Akbarian et al [ 33 ] reported that the phenolic compounds in plant extracts have an inhibitory effect on 3-hydroxy-3methylglutaryl coenzyme A, which is essential for cholesterol synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The key element in maintaining the productive birds' health is to provide the organ with natural bioregulators -biologically active substances. The in-depth study of the biochemical processes in birds' organisms and their morphological manifestations contribute to the creation of new types of feed and feed supplements, which best suit each individual species and breed [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%